Knock Knock/: My Dad's Dream for Me My Dad's Dream for Me - Beaty, Daniel; Collier, Bryan illustrator; Ling, Alvina editor; Bart-Horvath, Stephanie designer; Lopes, Jonathan production (New York: Little Brown and Company, 2013)
But what happens when, one day, that "knock knock" doesn't come? This powerful and inspiring book shows the love that an absent parent can leave behind, and the strength that children find in themselves as they grow up and follow their dreams.
Kids